Análisis de las estrategias de resolución de problemas de trigonometría en estudiantes de 15 a 17 años (2024)
This paper examines the problem-solving strategies and knowledge mobilized by 15–17-year-old students in trigonometry through the analysis of their answers to a questionnaire. To carry out this analysis, the four phases of problem solving proposed by Pólya and a model for classifying levels of understanding and knowledge in trigonometry were followed. The data collection and analysis process were carried out using MAXQDA software, which allowed for the segmentation and coding of the questionnaire responses, followed by the categorization of the codes identified. The results obtained indicate that students tend to solve trigonometry problems according to algorithms learned from previously solved exercises, without necessarily applying Pólya's four phases of problem solving. Furthermore, a generalized level of instrumental understanding is observed among students, suggesting that they use knowledge as a tool to solve problems without a deep understanding of the knowledge underlying the concepts and procedures used. A greater mastery of the trigonometry of triangles and the unit circle is highlighted in comparison to the knowledge of trigonometric function graphs. The results of this research may be useful for mathematics teachers or researchers who wish to design tasks that are consistent with the problem-solving strategies and level of knowledge mobilized by students.